Feasibility study for implementation of resuscitative balloon occlusion of the aorta in peri‐arrest, exsanguinating trauma at an adult level 1 Australian trauma centre. (22nd December 2019) - Fitzgerald, Mark; Lendrum, Robbie; Bernard, Stephen; Moloney, John; Smit, De Villiers; Mathew, Joseph; Kim, Yesul; Nickson, Chris; Lin, Richard M‐H; Yeung, Meei; Bystrzycki, Adam; Niggemeyer, Louise; et al.
Abstract: Objective: This prospective, observational, interventional study sought to determine if the introduction of resuscitative balloon occlusion of the aorta (REBOA) at an Australian adult major trauma centre would improve survival for major trauma patients. Methods: Patients aged 18–60 years, transported directly from scene with exsanguinating, sub‐diaphragmatic haemorrhage and hypovolaemic shock (systolic BP <70 mmHg or hypovolaemic cardiac arrest) were eligible for recruitment and followed up until hospital discharge (ACTRN12618000550202). Results: During the 14‐month study period (17 January 2015 to 12 March 2016) 3032 patients were admitted direct from scene with an overall mortality of 97 (3.71%). Of these patients 3019 had trauma centre vital signs recorded in the data set (99.57%) and 1523 were between the ages of 18–60, including 143 patients with a shock index of >1.0 (4.74%). There were 13 (0.43%) patients with a systolic BP <70 mmHg and/or cardiorespiratory arrest on arrival. The mortality in this group was six out of 13 (46.15%). Of these 13 patients, there were two (0.07% of the total cohort) where REBOA was attempted. There were no eligible patients for whom REBOA was achieved. None of the six patients who died would have benefited from REBOA deployment. Conclusions: Despite considerable training and resource allocation to ensure 24‐h availability, the introduction of REBOA failed to effectively demonstrate any impact on patient outcome. Despite retrospective literature supporting the introduction of REBOA, in this 14‐month prospective study there was no evidence of benefit. Further studies may define indications and subgroups of patients who may benefit.